Risk Stratification of Prostate Cancer Through Quantitative Assessment of PTEN Loss (qPTEN). (4th March 2020) - Jamaspishvili, Tamara; Patel, Palak G; Niu, Yi; Vidotto, Thiago; Caven, Isabelle; Livergant, Rachel; Fu, Winnie; Kawashima, Atsunari; How, Nathan; Okello, John B; Guedes, Liana B; Ouellet, Veronique; et al.
Abstract: Background: Phosphatase and tensin homolog (PTEN) loss has long been associated with adverse findings in early prostate cancer. Studies to date have yet to employ quantitative methods (qPTEN) for measuring of prognostically relevant amounts of PTEN loss in postsurgical settings and demonstrate its clinical application. Methods: PTEN protein levels were measured by immunohistochemistry in radical prostatectomy samples from training (n = 410) and validation (n = 272) cohorts. PTEN loss was quantified per cancer cell and per tissue microarray core. Thresholds for identifying clinically relevant PTEN loss were determined using log-rank statistics in the training cohort. Univariate (Kaplan-Meier) and multivariate (Cox proportional hazards) analyses on various subpopulations were performed to assess biochemical recurrence-free survival (BRFS) and were independently validated. All statistical tests were two-sided. Results: PTEN loss in more than 65% cancer cells was most clinically relevant and had statistically significant association with reduced BRFS in training (hazard ratio [HR] = 2.48, 95% confidence interval [CI] = 1.59 to 3.87; P  < .001) and validation cohorts (HR = 4.22, 95% CI = 2.01 to 8.83; P  < .001). The qPTEN scoring method identified patients who recurred within 5.4 years after surgery ( P  < .001). In men with favorable risk of biochemical recurrence (Cancer of the Prostate Risk Assessment – Postsurgical scores <5 and no adverse pathological features), qPTEN identified a subset of patients with shorter BRFS (HR = 5.52, 95% CI = 2.36 to 12.90; P  < .001) who may be considered for intensified monitoring and/or adjuvant therapy. Conclusions: Compared with previous qualitative approaches, qPTEN improves risk stratification of postradical prostatectomy patients and may be considered as a complementary tool to guide disease management after surgery.